Bioaugmentation strategy to enhance polycyclic aromatic hydrocarbons anaerobic biodegradation in contaminated soils. (July 2021) - Ferraro, Alberto; Massini, Giulia; Miritana, Valentina Mazzurco; Panico, Antonio; Pontoni, Ludovico; Race, Marco; Rosa, Silvia; Signorini, Antonella; Fabbricino, Massimiliano; Pirozzi, Francesco
Abstract: This paper proposes an innovative bioaugmentation approach for the remediation of polycyclic aromatic hydrocarbon (PAH) contaminated soils, based on a novel habitat-based strategy. This approach was tested using two inocula (i-24 and i-96) previously enriched through an anaerobic digestion process on wheat straw. It relies on the application of allochthonous microorganisms characterized by specific functional roles obtained by mimicking a natural hydrolytic environment such as the rumen. The inocula efficiency was tested in presence of naphthalene alone, benzo[a]pyrene alone, and a mix of both of them. In single-contamination tests, i-24 inoculum showed the highest biodegradation rates (84.7% for naphthalene and 51.7% for benzo[a]pyrene). These values were almost 1.2 times higher than those obtained for both contaminants with i-96 inoculum and in the control test in presence of naphthalene alone, while they were 3 times higher compared to the control test in presence of benzo[a]pyrene alone. In mixed-contamination tests, i-96 inoculum showed final biodegradation efficiencies for naphthalene and benzo[a]pyrene between 1.1 and 1.5 higher than i-24 inoculum or autochthonous biomass. Total microbial abundances increased in the bioaugmented tests in line with the PAH degradation. The microbial community structure showed the highest diversity at the end of the experiment in almost all cases. Values of the Firmicutes active fraction up to 7 times lower were observed in the i-24 bioaugmented tests compared to i-96 and control tests. This study highlights a successful bioaugmentation strategy with biological components that can be reused in multiple processes supporting an integrated and environmentally sustainable bioremediation system. Highlights: Bioremediation in anaerobic conditions of PAH contaminated soils was performed. Inocula enriched on wheat straw for 24 and 96 h were used for bioaugmentation. A novel bioaugmentation strategy with enriched inocula was tested for PAH removal. Bioaugmentation with allochtonous microorganisms promoted PAH degradation. Best multi-contaminated soil remediation was showed by 96 h enriched inoculum.